Calcitonin gene-related peptide predicts therapeutic response to midodrine hydrochloride in children with vasovagal syncope - Li, Lintian; Zhao, Huacai; Ma, Xiuxiu; Jiao, Fuyong; Lin, Jing (Frontiers in Neuroscience, 2022)
The vasoconstriction agent midodrine hydrochloride is a vital treatment for pediatric patients diagnosed with vasovagal syncope (VVS), although the efficacy is variable. This study was designed to explore the value of calcitonin gene-related peptide (CGRP) in predicting the effect of midodrine hydrochloride treatment upon VVS patients. In total, 55 children diagnosed with VVS were treated with midodrine hydrochloride for 3 months. Therapeutic response was evaluated using a symptom score system. CGRP levels were significantly higher in VVS patients (68.700±6.460) than in control subjects (43.400±5.810; t=18.207, P<0.001) and symptom scores correlated positively with CGRP concentrations (r=0.779, P<0.001). Patients treated with midodrine hydrochloride showed a significant reduction in symptom scores [4 (0, 6.5) vs. 1 (1, 2); z=-6.481; P<0.001]. However, the value of plasma CGRP were potently elevated in the positive-response subjects than in the nagetive-response subjects (70.080±5.040) vs. (61.150±3.090); t=5.817; P<0.001). The area under the ROC curve showed that the value of CGRP for predicting the therapeutic response to midodrine hydrochloride was 0.946 (95% CI: 0.879–0.997, P<0.001). With high sensitivity (97.7%) and specificity (83.3%), CGRP predicted the therapeutic response to midodrine hydrochloride (cut-off value, 62.56 pg/ml). In conclusion, CGRP can be used to predict the effect of midodrine hydrochloride administration in VVS patients.